Acute Abdominal Case Report: Ruptured Ovarian Endometriotic Cyst Concurrent with Acute Appendicitis - Nareswari, Gupita (Sanus Medical Journal, 2022)
Acute pain of pelvic origin is a common symptom necessitating emergent medical evaluation. Acute pelvic pain in young women can present as a unique diagnostic dilemma. Differential diagnosis in acute pelvis pain can vary according to risk. Possible causes span a gamut from functional ovarian cysts that require routine follow-up to adnexal torsion and ectopic pregnancy requiring urgent surgical management. This case report illustrates how concomitant gynecologic disorders can occur in patients with acute appendicitis. The laparoscopic operation revealed a ruptured ovarian endometriotic cyst concurrent with acute appendicitis and was proven by histopathology. This serves as a reminder that even though a rare case is contemporary, two different entities can occur.